Experimental Study on Mechanical Properties of Deep Buried Granite under Different Confining Pressures - Jun Zhao; Tan Zhang (Advances in Civil Engineering)
Brittle failure of hard rock poses a serious threat to the stability of surrounding rock in deep underground engineering. In order to study the deformation and failure characteristics of deep buried granite under high confining pressure cyclic loading and unloading, MTS815 electro-hydraulic servo rock test system was used to conduct cyclic loading and unloading tests under confining pressures of 15 MPa, 35 MPa, 45 MPa, and 55 MPa, and the corresponding stress-strain curves and deformation failure characteristic curves were obtained. The experimental results show the follows: (1) under the same confining pressure, the peak strength, crack initiation stress, crack damage stress, and Poisson’s ratio of the specimens under cyclic loading and unloading are larger than those under conventional triaxial loading and unloading, and the unloading elastic modulus is smaller than that, under conventional triaxial compression; (2) the results show that, under different confining pressures, the granite samples show obvious brittle failure characteristics, the elastic modulus and crack initiation stress increase first and then decrease with the confining pressure, the peak strength and crack damage stress of the samples increase linearly with the confining pressure, and Poisson’s ratio increases first and then remains unchanged with the confining pressure; (3) under the two kinds of stress conditions, the macroscopic failure of the samples is mainly shear failure. The deformation and failure law of granite samples revealed in this study has significant reference value for the selection of rock mass mechanical model of surrounding rock stability of underground engineering, the formulation of surrounding rock support countermeasures, and the evolution law of mechanical parameters with damage variables.